THE IMPORTANCE OF LEARNING ENGLISH TODAY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article explores the growing importance of learning English in the era of globalization, digital communication, and international cooperation. It analyzes the role of English as a global lingua franca in education, business, technology, and cultural exchange. The study highlights key socio-economic advantages of English proficiency, discusses modern approaches to language learning, and emphasizes how mastering English enhances individuals’ competitiveness in the global labor market. Furthermore, the article identifies the challenges learners face and proposes effective strategies for improving English acquisition in the 21st century.